Pendidikan Agama Islam sebagai Media Penguatan Karakter dan Mental Spiritual - Tajuddin Tajuddin; Amaluddin Amaluddin (FKIP UNSULTRA, 2025)
Islamic Religious Education (PAI) has a strategic role in shaping character and strengthening the spiritual mentality of students amidst the challenges of the era of globalization and disruption of moral values. Through an Islamic values ​​approach, PAI can be a foundation in building individuals with integrity, noble character, and strong mentality in facing social pressures and developments of the times. This study aims to examine various literature related to the contribution of PAI to strengthening the character and spiritual mentality of students, both in schools and outside schools. This study uses a literature study method (library research) by reviewing scientific journals, reference books, and education policy documents. The results of the study show that PAI is able to strengthen the values ​​of honesty, responsibility, empathy, discipline, and spiritual resilience of students. In addition, internalization of religious values ​​in PAI learning has a positive impact on students' inner peace and learning motivation. Character building through habituation methods, teacher role models, and integration of Islamic values ​​in daily life are the main strategies in implementing religion-based character education. Thus, PAI not only plays a role as a subject, but also as a medium for continuous character and spiritual development. This study recommends improving the quality of Islamic Religious Education teachers and integrating a more humanistic and contextual curriculum to strengthen the relevance and effectiveness of Islamic Religious Education in the modern era.